Pendekatan Hot-Fit Framework dalam Generalized Structural Component Analysis pada Sistem Informasi Manajemen Barang Milik Daerah: Sebuah Pengujian Efek Resiprokal - Erimalata, Shofana (Journal of Accounting and Investment, 2016)
This study aims to examines the determinant of the information quality of fixed assets on the accrual-based balance sheet using HOT-Fit Framework approach with Generalized Structural Component Analysis (GeSCA) method. The study using questionnaire with 90 respondents who represented all the local government agencies of Mataram City Government. Data anaylisis employs structural equation model (SEM). The study revelas there is a reciprocal relation between organizational controling and the information quality of fixed assets. The study also indicates that the software quality of Sistem Informasi Manajemen Barang Milik Daerah/Management Information System for Local Government’s Goods (SIMDA BMD) affecting the user satisfaction and organizational controling. The implications of these results can be used as consideration in adjusting the Mataram City Government accounting policy regarding fixed assets administration in order to produce quality information on fixed assets for the local government accrual-based balance sheet. Then, users of information system are needs to trained in order to increase competence to conduct the administration of fixed assets accrual based, so it can contribute to improve the quality of fixed asset information presented on the accrual based balance sheet.